Innovative moments and change in narrative therapy - Matos, Marlene (2009)
Narrative therapy suggests that change happens by paying close attention in therapy to "unique outcomes," which are narrative details outside the main story (White & Epston, 1990). In this exploratory study, unique outcomes were analyzed in five good-outcome and five poor-outcome psychotherapy cases using the Innovative Moments Coding System (Gonçalves, Matos, & Santos, 2008). Across 127 sessions, innovative moments were coded in terms of salience and type. In accordance with the theory, results suggest that innovative moments are important to therapeutic change. Poor- and good-outcome groups have a global difference in the salience of the innovative moments. In addition, results suggest that two particular types of innovative moments are needed in narrative therapy for therapeutic change to take place: re-conceptualization and new experiences. Implications for future research using this model of analysis are discussed.